2020
DOI: 10.4103/jfmpc.jfmpc_58_20
|View full text |Cite
|
Sign up to set email alerts
|

An institution-based study to assess the prevalence of Nomophobia and its related impact among medical students in Southern Haryana, India

Abstract: Background: Inappropriate usage of mobile phones is very hazardous for school and college students as it results in poor academic performance due to the poor concentration during classes or lectures over use of mobile phones, accidents due to reduced concentration while driving, and poor social relations due to preference for mobile usage and avoiding nearby people. Aim: Considering the above facts, the present study was conducted with an aim to estimate the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This is consistent with several studies, which demonstrated a strong association between nomophobia and sleep problems (mainly insomnia) [3,[27][28][29][30]48,49]. A direct relationship was found between the nomophobia score of medical students and sleep quality, measured by the Pittsburgh sleep quality index (PSQI) [50]. Likewise, a one-year prospective study among young Swedish adults revealed increased mobile phone addiction behaviors in individuals with higher baseline scores of sleep problems [51].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with several studies, which demonstrated a strong association between nomophobia and sleep problems (mainly insomnia) [3,[27][28][29][30]48,49]. A direct relationship was found between the nomophobia score of medical students and sleep quality, measured by the Pittsburgh sleep quality index (PSQI) [50]. Likewise, a one-year prospective study among young Swedish adults revealed increased mobile phone addiction behaviors in individuals with higher baseline scores of sleep problems [51].…”
Section: Discussionsupporting
confidence: 90%
“…India contributed with seven studies [2,3,[15][16][17][18][19][20], Iran [21,22], Turkey [1,23], and Pakistan [24,25] contributed each with two studies, and Australia [26], Bahrain [8], Israel [27], Italy [28], Kuwait [29], and USA [30] each contributed with one study. Fourteen studies [2,[15][16][17][19][20][21][22][23][24][25][28][29][30] (70%) of the studies recruited university students as participants, while four studies [8,18,27,28] (20%) recruited young adults and only two studies [1,3] (10%) recruited high school students. The NMP-Q was used in 12 studies [1,3,8,17,19,[24][25][26]…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the majority of the studies included in this systematic review and meta-analysis have used the same well-established measurement tool, which is the NMP-Q, has increased the quality and simultaneously decreased the bias of the study. The pooled prevalence of severe nomophobia, using the NMP-Q tool, was estimated to be 16 Most of the studies that were included in the analysis were conducted in India and the Middle East. On the contrary, the lack of studies reported from other regions, such as Eastern Europe and China, has limited the reliability of the global pooled prevalence obtained from this study.…”
Section: Discussionmentioning
confidence: 99%
“…The main drawbacks of nomophobia among students are sleep disturbances and poor academic achievement. A study done in India in 2020 shows that addiction to mobile phones reflects poor academic performance for school and college students [ 6 ]. Nomophobia affects not only the academic performance of students but also their lives with anxiety, depression, high stress levels, low physical activity, and a higher body mass index (BMI) [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%